PENGARUH ELECTRONIC WORD OF MOUTH DAN HARGA TERHADAP KEPUTUSAN PEMBELIAN ONLINE DI MARKETPLECE SHOPEE (Lembaga Pengembangan Kinerja Dosen, 2022)
This study aims to test and analyze the effect of electronic word of mouth and price on online purchasing decisions. This research was conducted on the Shopee Marketplace case study on ITB Student Ahmad Dahlan Lamongan. The sample of this study was 45 respondents using random sampling techniques. The data were analyzed using multiple linear regression analysis, classical assumption test, T test, and Coefficient of Determination with SPSS 26 software. The results showed that partially there was a significant influence of Electronic Word Of Mouth variables on Online Purchase Decisions, Price Variables had a significant influence on Online Purchase Decisions